2020
DOI: 10.1101/2020.12.23.20248425
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical practices underlie COVID-19 patient respiratory microbiome composition and its interactions with the host

Abstract: Understanding the pathology of COVID-19 is a global research priority. Early evidence suggests that the microbiome may be playing a role in disease progression, yet current studies report contradictory results. Here, we examine potential confounders in COVID-19 microbiome studies by analyzing the upper (n=58) and lower (n=35) respiratory tract microbiome in well-phenotyped COVID-19 patients and controls combining microbiome sequencing, viral load determination, and immunoprofiling. We found that time in the in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 63 publications
1
7
0
1
Order By: Relevance
“…A common feature in MADs is that commensal/neutral bacteria can become pathogenic at the face of disease 21 . That is the case of bacteria such as g_ Prevotella , g_ Veillonella , g_ Streptococcus , g _Actinomyces , or g_ Megasphaera , which have been found as opportunistic pathogens in other studies characterizing COVID-19 microbiota 12,1921 and that were also found in this work (severe and fatal associated microbiota (Fig. 2B)).…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…A common feature in MADs is that commensal/neutral bacteria can become pathogenic at the face of disease 21 . That is the case of bacteria such as g_ Prevotella , g_ Veillonella , g_ Streptococcus , g _Actinomyces , or g_ Megasphaera , which have been found as opportunistic pathogens in other studies characterizing COVID-19 microbiota 12,1921 and that were also found in this work (severe and fatal associated microbiota (Fig. 2B)).…”
Section: Discussionsupporting
confidence: 72%
“…For mild COVID-19, we found some microbial groups associated with disease or bacteremia like g_ Prevotella melaninogenica , g_ V. parvula and g_ Neisseria subflava 7,28 . For the case of severe COVID-19, we found g_ Megasphaera that has been associated with the risk of ventilator-associated pneumonia (VAP) in other studies characterizing COVID-19 microbiota 12 . Additionally, we found g_ Rothia dentocariosa highly abundant in deceased patients.…”
Section: Discussionmentioning
confidence: 64%
“…A major confounding factor is that therapeutic interventions may influence the microbiome in COVID-19 [48], with treatments such as antibiotics and mechanical intervention co-occurring with more severe disease (see Table 1). Bradley et al sought to avoid this by sampling the oropharyngeal microbiome at hospital admission and predicting the future need for respiratory support [49].…”
Section: Oropharyngeal Microbiome Associations With Covid-19 Severity...mentioning
confidence: 99%
“…Studies profiling patients prior to treatment avoid this effect (i.e., Bradley et al [49]). Other studies with both COVID and non-COVID-19 patients receiving antibiotics can identify the effect of specific antibiotics, which can then be separated from the effects of COVID (i.e., Lloréns-Rico [48])…”
Section: Antibiotic Usagementioning
confidence: 99%
“…Overall, they confirmed predominance of multiple pathobionts and oral commensal bacteria in lower respiratory tract samples 5 9 , the latter supporting the idea of micro-aspiration of oral microbes as a source of lung colonization and infection. Some studies have already linked the composition of microbial communities with COVID-19 disease severity 8 , 10 , 11 . Most of these studies confirm similar patterns in COVID-19 patients compared to patients diagnosed with community-acquired pneumonia in the pre-pandemic era 6 .…”
Section: Introductionmentioning
confidence: 99%